PENGARUH KONSENTRASI ASAM DALAM PEMBUATAN GONDORUKEM MALEAT TERHADAP RENDEMEN DAN SIFAT FISIKO-KIMIANYA - Bambang Wiyono (Pusat Penelitian dan Pengembangan Hasil Hutan, 2002)
Rosin is a mixture of abietic and pimaric acids with small amount of neutral materials. By modifying these acids could widen its utilizations. One of modified rosin is maleic rosin. This study is intended to find out the effect of acid concentration on yield and maleic rosin physico-chemical properties. The research target is to determine a proper condition for manufacturing of maleic rosin which could fulfill the standard requirements.The manufacturing of maleic rosin was carried out by elevating the temperature to 160 - 170 °C and maintained it at this temperature for 2-3 hours. Maleic acid that was used in the process consisted of 0 %, 2%. 4%, 6% and 8%. The physico-chemical properties of the maleic rosin produced was analysed. As raw materials. this experiment utilized rosin from North Sumatra (WW quality) and rosin from East Java (WG quality). The phsyco-chemical properties of the products were then analysed. The data were analysed by using factorial random design, and the different value between means was calculated with Tukey procedure by the SAS computer package.The results showed that the increase in maleic acid concentration caused to increase in yield, softening points. acid value. and saponification value of maleic rosin. The ash content value, however, did not exhibit certain tendency when maleic rosin were produced under the experimental condition applied. Rosin from East Java with WW quality produced maleic rosin higher softening point and saponification value than that of from North Sumatra with WG quality. Based on its softening point and dirt content, manufacturing maleic rosin with acid concentration 2 % in this experiment produced maleic rosin which could meet the requirement of second quality for Chinesse maleic rosin.